Nos passos da “Festividad de la Santísima Trinidad del Señor Jesús Del Gran Poder" : um olhar folkcomunicacional para as danças da Bolívia - Terán Machicado, Karla Andrea (2020)
ABSTRACT: The festival known as "La Festividad de la Santísima Trinidad del Señor Jesús del Gran Poder" is the largest folkloric event in the city of La Paz (Bolivia), a moment that brings together and mixes the different socio-cultural groups of the paceña society, as people from different social, economic and family strata come together to give prestige to the event, where cultural and religious syncretism is present. It can be said that folklore is a vital component within a society, the interest in carrying out a study on this festival is justified, observing its practices, festive rituals and especially the dances presented in its course because they represent a central way of communication of the festival. This study has been developed in the field of social and cultural practices and more specifically within the theory of folk communication, guided by the theoretical and methodological contributions of Luiz Beltrão, the creator of this theory. For this reason, the objective of this research is to carry out a folkcommunicational analysis of the festival, researching in what ways it acts as a popular cultural production for the promotion of communication of the marginalized and of folklore as a socio-cultural practice. The approach is qualitative and the methodology is developed from the theoretical and documentary analysis of a series of researches linked to the folk communicational field. In this sense, the fieldwork is developed through direct observation and semi-structured interviews conducted with some participants of the party. The reflective challenge points to the inclusion of other theoretical categories that were absent in previous work on Bolivian folklore, to support the idea that folklore implies communicational processes, which allow us to understand a certain society, and how individuals resynthesize codes, practices and meanings linked to their own culture over time to speak of this festival as an expression of cultural resistance.